Study of intracellular signaling pathways in Chronic Myeloproliferative Neoplasms - Martinelli, Serena (Premio Tesi di Dottorato, 2017)
A gain-of-function mutation in Janus kinase 2 (JAK2V617F) is at the basis of the majority of chronic myeloproliferative neoplasms (MPN). Enhanced activation of other downstream pathways including the PI3K/mTOR pathway has been documented as well. In this study we evaluated the effects of JAK1/2 inhibitors, alone and in combination with mTOR, with a dual mTOR/PI3K inhibitor and with a pan PI3K inhibitor in in-vitro and in-vivo MPN models. Our findings of strong synergy between the JAK2 inhibitors and mTOR/PI3K inhibitor suggested that we might be able to administer these drugs at lower concentrations than when the drugs are used individually. This provides a framework for combination trials using compounds in patients with myeloproliferative neoplasms